Sinergi Pengembangan Objek Wisata dan Pembangunan Ekonomi Masyarakat Desa - Hakim, Lukmanul; Lutfi , Ahmad Zaini (Mabny: Journal of Sharia Management and Business, 2023)
It is a human need to fulfill the desire to have fun and enjoy life. The demand for these needs can be realized by providing tourism places. From the supply side, the provision of these tourist spots can be utilized to develop the economy. One of the tourist attractions on the north coast of Madura Island is the Lon Malang monitor. This tourist spot is the result of cooperation between the local government, private bodies and the community to manage and organize. Managers involve a lot of local communities to develop this tour. Thanks to the development of this tourist spot, the economic impact has begun to be felt by the surrounding community. There are two focuses in this research, namely how to develop tourism and how the impact of Lon Malang tourism in improving the community's economy. This study uses a descriptive qualitative approach, collecting data by conducting interviews, observation and documentation. The results showed that, firstly, the development of Lon Malang beach tourism started with the initiative of the village head and community groups in Bira Tengah village, in the development of Lon Malang beach tourism prioritizing beauty without throwing away local culture (local wisdom). Secondly, the development of Lon Malang tourism can help increase the income of the people of Bira Tengah village, where initially many residents work as farmers and fishermen, with minimal income levels. After the development of this tour, many people are involved so that there are additional business opportunities, can increase income. regions and villages, and can increase the income of the people of Bira Tengah Village.